Penerapan Komponen Pelayanan Antenatal Care (10T) Dengan Kunjungan Ibu Hamil (K4) Di Puskesmas - Ririn Widyastuti (JURNAL KESEHATAN PRIMER, 2021)
Background: The maternal mortality rate (MMR) is an indicator of the degree of women's health. The cause of AKI is due to the knowledge about prevention of pregnancy, childbirth, postpartum and the lack of even good midwifery services for all pregnant women. Quality ANC services have an inspection service indicator in the form of 10T. Formulation of the problem in this research is how is the implementation of the implementation of antenatal care by midwives at the Kupang City Health Center in 2018? The research objective was to determine the implementation of the components of antenatal care services by midwives at the Kupang City Health Center in 2018. This type of research was an analytic observational study with a cross sectional research design. The population is 30 midwives who work in the MCH clinic in the Puskesmas in Kupang City. The sampling technique was saturated sample/total population. Data collection techniques using questionnaires and secondary data collection from PWS KIA. Data analysis using univariate in the form of frequency distribution tables and bivariate with Chi Square. The results of the study: 21 respondents (70%) had implemented the component of antenatal care services and 9 respondents (30%) had not implemented the components of antenatal care services and 6 health centers (60%) had not reached the target. Based on the statistical test of Fisher's exact test, the Exact Sig (2-sided) value or p value: 249 is obtained. A large p-value of 0.05 indicates that the hypothesis is rejected, which states that there is no relationship between the implementation of the components of antenatal care services by midwives with service coverage. ANC at the Fourth Visit (K4).